ANALISIS EFEKTIVITAS KOMUNIKASI BISNIS DALAM KEGIATAN OPERASIONAL DINAS PEKERJAAN UMUM BINA MARGA PROVINSI JAWA TIMUR - Trisna Novitasari; Binti Shofiatul Jannah (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
The purpose of this study was to determine the strength of the influence of communication on work effectiveness at the Sidrap Regency Public Works and Bina Marga Office. The sample was taken as many as 25 respondents. The research conducted by researchers is verification research or causality, which is research that looks for the relationship between the cause variable and the effect variable. The relationship in question is the relationship between Communication (Independent variable) and Work Effectiveness (Dependent variable). The analytical tool used is the Spearman Rank coefficient formula (ρ) Based on the analysis of the data collected, the following conclusions can be drawn: 1) The results of the analysis show that Communication is associated with Work Effectiveness. This shows that the more effective the communication that occurs, the work effectiveness will increase, on the other hand, if communication is ineffective, the work done will become increasingly ineffective. 2) Communication that occurs in the environment at the Sidrap Regency Public Works and Highways Office is quite effective, because after all the role of the leader here cannot be ruled out, because it is the leader who creates environmental conditions to be pleasant or otherwise.